The Assessment of the Supply of Calcium and Vitamin D in the Diet of Women Regularly Practicing Sport - Michał Wrzosek; Jakub Woźniak; Dorota Kozioł-Kaczorek; Dariusz Włodarek (Journal of Osteoporosis)
Introduction. The appropriate intake of calcium and vitamin D in women’s diet is significant for a proper maintenance of the skeletal system. Research Aim. The aim of the research was to assess the calcium and vitamin D supply in a diet among women regularly practicing sport. Methodology. The research was completed by 593 women at the age of 18–50 (median 25) who played sports regularly (at least 2 times a week). To assess the calcium and vitamin D intake, short Food Frequency Questionnaires for calcium and vitamin D (VIDEO-FFQ) were used. The examined group was provided with the questionnaires via social media. To assess intake levels, the authors applied the group-based cutoff point method (calcium norm was EAR 800 mg/day; vitamin D norm was AI 15 μg/day). Results. The median of calcium and vitamin D intake in a diet was 502 mg/day and 5.2 μg/day, respectively (Q25 and Q75 for calcium was 387 mg/day and 627 mg/day, respectively, and for vitamin D was 3.4 μg/day and 8.2 μg/day, respectively). In relation to the EAR norm for calcium and AI norm for vitamin D, 92.0% of the examined participants in a group demonstrated lower than recommended calcium intake levels and 97.3% showed lower than recommended vitamin D intake levels. Calcium and vitamin D supplementation was used by 13.1% (in this subgroup, 11.5% of the examined group members did not need it) and 56.8% of the examined women (in this subgroup, 2.4% of the examined group did not need it), respectively. After including the calcium and vitamin D intake, the supply median for the whole group was 535 mg/day and 28.8 μg/day, respectively (Q25 and Q75 for calcium was 402 mg/day and 671 mg/day, and for vitamin D was 6.3 µg/day and 55.7 μg/day, respectively); 87.5% of the examined participants did not meet the EAR norms for calcium and 42.0% did not meet the AI norm for vitamin D. Among the women supplementing calcium, 58.9% did not reach the reference intake value; however, all women supplementing vitamin D fulfilled the expected nutritional need. Conclusions. It is important to educate women about the necessity to provide the body with proper calcium and vitamin D intake levels in a diet in order to avoid health problems resulting from the deficit of the nutrients.